Integration of Murotal Art in Peer Counselling for the Development of Subjective Well-Being - Sugiyadi Sugiyadi; Astiwi Kurniati; Nofi Nur Yuhenita (International Journal of Multi Discipline Science (IJ-MDS), 2023)
The study of subjective well-being is a very important and urgent need now and in the future especially in Islamic boarding schools as a culture of education in Indonesia. The research aimed to develop subjective well-being through the integration of murotal art in peer counselling. The research method was quasi-experimental action research, namely carrying out an initial assessment, providing treatment, and a final assessment. The research subjects were 273 male students at the Al-Mukmin Muhammadiyah Tembarak Temanggung Islamic Boarding School as the population, and 17 male students as samples based on random sampling technique with subjective well-being as the problem variable and the integration of murotal arts and peer counselling as the intervention variable. The data collection technique used closed questionnaire instruments, and then data analysis used descriptive analysis. The results showed that there was an increase in the average subjective well-being score of 19.16 (15.45%) which was confirmed by understanding and changes in behaviour in self-acceptance, opening up, and networking. These findings were evidence that the integration of murotal art in peer counselling can be used to develop subjective well-being.